Odpowiedź:
-3−3
Wyjaśnienie:
Rozszerzanie
(x + x_1) (x + x_2) (x + x_3) (x + x_4) (x+x1)(x+x2)(x+x3)(x+x4) i porównanie mamy
{(x_1x_2x_3x_4 = -1), (x_1 x_2 x_3 + x_1 x_2 x_4 + x_1 x_3 x_4 x x 2 x_3 x_4 = 4), (x_1 x_2 + x_1 x_3 + x_2 x_3 + x_1 x_4 + x_2 x_4 + x_3 x_4 + x_2 x_4 + x_3 x_4 = -3), (x_1 + x_2 + x_3 + x_4 = -2):}
Analiza teraz
x_1 x_2 + x_1 x_3 + x_2 x_3 + x_1 x_4 + x_2 x_4 + x_3 x_4 = x_1x_2 + x_1x_3 + x_2x_4 + x_3x_4 + (x_2x_3 + x_1x_4)
Wybór x_1x_4 = 1 następuje x_2x_3 = -1 (patrz pierwszy warunek)
stąd
x_1x_2 + x_1x_3 + x_2x_4 + x_3x_4 + (x_2x_3 + x_1x_4) = -3 lub
x_1x_2 + x_1x_3 + x_2x_4 + x_3x_4 = -3- (x_2x_3 + x_1x_4) = - 3